New aspects of investigating stress, anxiety, and depression in the Ryazan region population with arterial hypertension - Ayoub Glenza; Natalia V. Dobrynina; Sergey S. Yakushin; Alexander A. Dzekan (КардиоСоматика)
BACKGROUND: Arterial hypertension is often accompanied by stress, anxiety, and depression that worsen the quality of life and prognosis of the disease. Global data on high anxiety and depression highlight the need to assess them in people with hypertension. This study in the Ryazan region will reveal the social and economic impact on the mental health of hypertensive patients.